HEAVY METAL, ORGANOCHLORINE PESTICIDE AND POLYCHLORINATED BIPHENYL CONTAMINATION IN ARCTIC GROUND SQUIRRELS (SPERMOPHILUS PARRYI) IN NORTHERN ALASKA - Susan Allen-Gil; DIXON LANDERS; T Wade; J Sericano; B Lasorsa; E Crecelius; L Curtis (ARCTIC V.50(4): 323-333, 2005)
Heavy metal and organochlorine (OC)concentrations, including organochlorine pesticides and polychlorinated biphenyl congeners (PCBs), were determined in arctic ground squirrels (Spermophilus parryi) from three sites in the Brooks Range of northern Alaska in 1991-93. Heavy metals were present in most squirrel livers collected, with concentrations of trace elements (As,Cd,Hg,Ni,and Pb) averaging below 1 mug/g wet weight. Hexachlorobenzene (HCB),p,p'-DDE, gamma hexachlorocyclohexane (gamma-HCH), tans-nonachlor, and PCBs 138,153,and 170 were the most frequently detected OCs in fat and liver. Average concentrations of individual OC analytes were below 20 ng/g wet weight in liver and below 15 ng/g wet weight in fat. Rank correlations indicate that concentrations of heavy metals and of OCs accumulate in concert with one another (As,Cd,Cu,and Zn, PCBs 138,170 and 180. Although heavy metal and OC concentrations are low relative to other areas and other arctic species, the occurrence of these compounds illustrates the global pervasiveness of persistent organic compounds and the potential for bioaccululation in the terrestrial arctic food web.